Features of organizing tourism services in the condition of digitalization - Sevinchova Nilufar Ne’mat qizi (Global Scientific Publishing, 2024)
The service sector occupies a dominant position in the economy of many countries of the world with different political systems, levels of economic development, territory, population and socio-cultural characteristics. The socio-economic development of the service sector, according to its content, is aimed at increasing quality of life, creating optimal conditions for the development of human capital associated with the formation of modern industries, and the distribution of a relatively high level of division of labor. covers various directions of economic activity.
Keywords: Digitalization; service; tourism; customer